334 GEMS: Geriatric Emergency Service - Rockwood's Clinical Frailty Scale and Outcomes. (16th September 2019) - Reddy, Danielle; Gallagher, Grainne; O'Callaghan, Maureen; Cornally, Lorna; Hayes Brennan, Megan; Mulholland, Ann; Nolan, Jane; Normoyle, Cathriona; Ahern, Emer; Gibbons, Ruth
Abstract: Background: Rockwood's Clinical Frailty Scale (CFS), which uses clinical descriptors and pictographs, was developed to provide clinicians with an easily applicable tool to stratify older adults according to level of vulnerability. The CFS was validated in a sample of 2305 older participants from the Canadian Study of Health and Aging and was shown to be a strong predictor of institutionalisation and mortality (Rockwood K, 2005). Methods: The aim of GEMS is to improve care, outcomes and the patient experience for older people living with Frailty. All people aged 75 years and older who attend as an emergency are screened on triage using the Variable Indicative of Placement Tool (VIP). The GEMS Acute Floor Team respond early to those who screen positive by starting a CGA. At the end of CGA all patients have a score 1 to 9 assigned from the Clinical Frailty Scale (CFS). Results: 10, 037 patients were triaged in the first two years of the service. 43% screened positive for Frailty. 66% had a CGA. 10% were vulnerable CFS 4, 32% mildly frail CFS 5, 32% moderately frail CFS 6 and 31% severely frail CFS 7. Increasing score on the CFS correlated with increased length of stay, death and institutionalisation. Conclusion: The CFS correlates with Length of stay (LOS), mortality and institutionalisation in people aged 75 years and older who attend as an emegency and screen positive for Frailty.